2016
DOI: 10.14687/jhs.v13i2.3769
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in regard to factors affecting the professional development of science teachers

Abstract: As one of the crucial elements of education system, teachers' professional development is important to equip them with the education to compensate the needs of modern life. The major aim of this research is to determine the views of school principals and science teachers on the concept of professional development, and identify factors which affect science teachers' professional development. Both qualitative (semi-structured interview) and quantitative (survey) research methods were used in the research. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
5
0
1
Order By: Relevance
“…For this reason, teachers especially in the field of science should be encouraged to develop their competencies, especially their skills, dispositions to teaching, attitudes towards students during the pre-service and in-service training. Furthermore, they should also take over responsibility of their self-development to contribute to their professional development realistically (Kaya & Godek, 2016). On the other hand, the dimension of teaching has the positively effect on environmental literacy.…”
Section: Discussion Implications and Recommendationsmentioning
confidence: 99%
“…For this reason, teachers especially in the field of science should be encouraged to develop their competencies, especially their skills, dispositions to teaching, attitudes towards students during the pre-service and in-service training. Furthermore, they should also take over responsibility of their self-development to contribute to their professional development realistically (Kaya & Godek, 2016). On the other hand, the dimension of teaching has the positively effect on environmental literacy.…”
Section: Discussion Implications and Recommendationsmentioning
confidence: 99%
“…Other scholars have found that teachers' professional experience, teaching skills, and disposition influence educational practice [51]. In general, teachers gain professional experience in a process that begins with pre-service training and continues with in-service training [52]. Brekelmans et al (2005) discussed the role of teacher experience in education and revealed two factors-specifically, time for acquiring the skills necessary to face challenges and enthusiasm for change and innovation-that implicate the usefulness of training [49].…”
Section: Establishment Of Hypothesesmentioning
confidence: 99%
“…Teachers' professional experience, teaching skills, and disposition influence the training of qualified environmentally literate individuals (Kaya and Elster, 2018). In general, teachers gain their professional experience in a process that begins with pre-service training and continues with in-service training (Kaya and Gödek, 2016 1 and Figure 1). In the view of Shulman (1986), PCK:…”
Section: The Effect Of Pedagogical Content Knowledge (Pck) and Teachers' Professional Developmentmentioning
confidence: 99%